THE STATE OF POPULATION HEALTH IN THE CZECH REPUBLIC, GREECE AND SWEDEN - -, Irina; Langhamrová, Jitka, 1958-; Svačinová, Kornélia; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2018)
The bachelor thesis analyses and compares the state of population health in the Czech Republic, Greece and Sweden – countries situated in contrasting regions of the European Union with the very high Human Development Index, but with completely different history, different political and socioeconomic conditions. The work is divided into two parts. The first one is theoretical and is focused on basic concepts and terminology related generally to health and to the state of population health and its measurement. Furthermore, this part includes an information about the European Health Interview Survey (EHIS) which results are used in the final part of the thesis. The following practical part introduces general information about the selected countries, their basic demographic characteristics, and provides a detailed analysis of the evolution of population health indicators between 1996 and 2014, such as total mortality, causes of death, infant mortality, life expectancy, Healthy Life Years. The last part also provides an overview of the EHIS 2014 results in the selected states.
Vedoucí práce: Jitka Langhamrová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: sociálně ekonomická demografie [obor bakal. práce]; bakalářské práce; bachelor's theses